2017
DOI: 10.21767/2049-5471.1000112
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Platelet-rich Plasma (PRP) Compared to Ozone Infiltrations on Patellofemoral Pain Syndrome and Chondromalacia: A Non- Randomized Parallel Controlled Trial

Abstract: Objective: 1) to determine the efficiency of PRP compared to Ozone Infiltrations on pain, function and quality of life (QoL) in patients with Patellofemoral Pain Syndrome (PFPS) and Chondromalacia. Material and methods:Prospective non-randomized controlled-trial, comparing two treatment protocols in parallel design, on 48 patients (24 in each group), with PFPS and Chondromalacia , who were treated at Santa Cristina's University Hospital, from January 2014 to May 2017. The PRP-protocol consisted of 3 sessions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Recently, a study compared ozone (O 2 -O 3 ) to PRP in the management of chondromalacia, considered by many as a pre-stage of knee OA, and the results obtained were very promising (22). For this reason, the researchers hypothesized that ozone (O 2 -O 3 ) could also be as effective as PRP in the management of established knee OA (from mild to moderate and even severe stages), a fact that has been clearly demonstrated in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study compared ozone (O 2 -O 3 ) to PRP in the management of chondromalacia, considered by many as a pre-stage of knee OA, and the results obtained were very promising (22). For this reason, the researchers hypothesized that ozone (O 2 -O 3 ) could also be as effective as PRP in the management of established knee OA (from mild to moderate and even severe stages), a fact that has been clearly demonstrated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…By doing this, a final 3-mL volume of PRP concentrate was obtained. This technique has been explained earlier by the study group (21,22).…”
Section: Prp Treatmentmentioning
confidence: 99%
“…When the patella has a different orientation, it will glide to one side of the patellar facies of the femur, which may cause overuse and overpressure on that part of the femur, resulting in pain, discomfort or irritation. 3 The prevalence of PFPS based on a systematic review conducted by Smith et al in the general population in the UK (2017) was 22.7%, in men as much as 15.5%, and in women, both adolescents and young adults, the highest prevalence of 29.2%. 4 A retrospective review of the orthopaedic database showed more than 30 million patients in the United States in 2007-2011; 1.75 million patients (about 6%) experienced PFPS, and women accounted for 55% of cases.…”
Section: Introductionmentioning
confidence: 99%